2016
DOI: 10.1128/jvi.02774-15
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Interferon-Regulatory Factor 1 Counteracts the Germinal Center Reaction Driven by a Cancer-Associated Gammaherpesvirus

Abstract: Gammaherpesviruses are ubiquitous pathogens that are associated with the development of B cell lymphomas. Gammaherpesviruses employ multiple mechanisms to transiently stimulate a broad, polyclonal germinal center reaction, an inherently mutagenic stage of B cell differentiation that is thought to be the primary target of malignant transformation in virus-driven lymphomagenesis. We found that this gammaherpesvirus-driven germinal center expansion was exaggerated and lost its transient nature in the absence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…This suggests that, at least during acute MHV68 infection, IRF-1 functions are complemented by type I IFN expression and signaling. In contrast, we showed that IRF-1 Ϫ/Ϫ mice have poor control of chronic MHV68 infection (23), indicating that type I IFN signaling is no longer able to compensate for IRF-1 deficiency once gammaherpesvirus infection becomes chronic. (33).…”
Section: Discussionmentioning
confidence: 41%
“…This suggests that, at least during acute MHV68 infection, IRF-1 functions are complemented by type I IFN expression and signaling. In contrast, we showed that IRF-1 Ϫ/Ϫ mice have poor control of chronic MHV68 infection (23), indicating that type I IFN signaling is no longer able to compensate for IRF-1 deficiency once gammaherpesvirus infection becomes chronic. (33).…”
Section: Discussionmentioning
confidence: 41%
“…In contrast to the positive role of IRF8 in EBV lytic replication observed in our study, most of the IRFs contribute to anti-viral immunity and block the infection or lytic reactivation of herpesviruses. For example, it was reported that IRF1 restricts gammaherpesvirus replication through IFN-mediated suppression of viral replication [ 73 , 74 , 75 , 76 ]. IRF2 also suppresses gammaherpesvirus replication and reactivation by inhibiting the M2 gene promoter [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elucidation of oncoprotein-mediated inhibition of transactivating IRF activity during HPV infection has reinforced the conceived supposition that immune response and viral immune evasion may be intimately tied to cancer (Park et al, 2000; Ronco et al, 1998; Um et al, 2002). IRF-1 has been characterized as a tumor suppressor based on the presence of low IRF-1 levels in a number of human cancers, its function in promoting apoptosis and suppressing cell proliferation in vitro , as well as the correlation between loss of IRF-1 and oncogene deregulation in vivo (Mboko et al, 2016; Nozawa et al, 1999; Savitsky et al, 2010). Furthermore, epidemiological studies have proposed that viral evasion factors of cellular immunity can be etiological agents of oncogenesis (Um et al, 2002).…”
Section: Viral Hijacking Of Host Defense Proteinsmentioning
confidence: 99%